Planning of Evacuation Places and Routes for Flood Disaster in Kesambi District, Cirebon, Indonesia - Mohammad Rivaldy; Sobar Sutisna; Robertus Anugerah Purwoko Putro; Rachmat Setiawibawa; Subiyanto, Adi; Sutanto (UIR PRESS, 2025)
The increasing frequency and intensity of flooding in Kesambi District, Cirebon City, has caused significant economic losses and disrupted people's lives. This study attempts to manage flood disaster risks through careful planning. By combining spatial data analysis and an associative descriptive approach, this study produces a map of evacuation places and routes that can be relied on to deal with future floods. The results of the study indicate that the potential for flooding in Kesambi District causes extensive damage and has a significant impact on people's lives, especially in Drajat, Kesambi, and Pekiringan Sub-districts. Thousands of residents of Kesambi District are exposed to disaster risks and damage to buildings and infrastructure that hinder mobility and economic activity. Based on the analysis of capacity, travel time, and distance, this study has determined 6 evacuation places that can accommodate the estimated number of evacuees and 40 existing evacuation routes can be safely passed. These six evacuation places are considered strategic because they are close and can be reached in a short time, making it easier for people to immediately carry out independent evacuation when a disaster occurs.